Molecular Evaluation of Plasmodium falciparum Drug Resistant Genes Among Pregnant Women Attending ANC at Maryam Abacha Women and Children Hospital (MAWCH) Sokoto, Nigeria - Abubakar, Hafiz; Bala Yabo, Aminu; Muhammad Bandiya, Haliru; Bello Shuaibu, Abdulmalik (Journal of Current Biomedical Research, 2022)
Research was conducted on the molecular survey of drug resistant Plasmodium falciparum malaria among pregnant women attending ante natal care (ANC) at Maryam Abacha Women and Children Hospital (MAWCH) Sokoto, Nigeria from February, 2020 to May, 2020. Blood samples of 200 pregnant women who came for ANC in the Hospital were collected and Questionnaire administered. Thin and thick blood film microscopy and Plasmodium falciparum mono clonal antibody specific RDT kit were used to detect Plasmodium falciparum. P. falciparum positive dried blood samples were investigated for the presence of Pfmdr1 and Pfcrt genes using PCR protocol. Results for the investigation of Pfcrt and Pfmdr1 genes revealed 26.30% and 89.50% prevalence respectively, while 4 samples were positive for both genes representing 21.05% prevalence. Prevalence of Pfcrt and Pfmdr1 genes do not associate (p>0.05) with any of the parameters tested. Spread of the mutant genes observed in this study may be attributed to the continuous use of antimalarial drugs that the parasite developed resistant to. Pregnant women should be attending early ante-natal care booking and attend clinic regularly, malaria control programs should be carried out in the state.